Understanding Financial Risk Dynamics: A Qualitative Inquiry into Credit, Market, and Operational Risks in Banking, Investment, and Corporate Sectors - Sapiri, Muhtar (Manunggal Halim Jaya, 2025)
This qualitative study explores the dynamics of financial risk management, specifically focusing on credit, market, and operational risks within the banking, investment, and corporate sectors. The research investigates the interconnected nature of these risks, their implications for risk management practices, and their impact on systemic stability. The research methodology involves a comprehensive review of existing literature and qualitative interviews with experts in the field. Thematic analysis is employed to identify recurring themes and patterns within the data. The findings highlight the intricate interconnections between different types of risks and underscore the importance of adopting integrated risk management frameworks. The analysis shows that events associated with one kind of risk can have far-reaching implications for others, amplifying overall risk exposures and vulnerabilities. The study emphasizes the need for a holistic approach to risk management that considers the interdependencies between credit, market, and operational risks. The implications for risk management practices, regulatory frameworks, and systemic stability are discussed, highlighting the significance of enhancing operational resilience and promoting collaboration between academia, industry, and regulatory bodies. Overall, the research contributes to a deeper understanding of financial risk dynamics and provides insights for enhancing risk management practices within the economic system.